Development of self-assessment scale of Public health nursing Art to enhance “Strength of Community” (PASC) - Miho Tanaka; Reiko Okamoto; Keiko Koide; Misaki Kiya (BMC Nursing)
Abstract Background In recent years, health needs have become more complex and serious in Japan, and technologies that enhance local strengths to solve problems are essential. It is essential to develop a learning programme for public health nurses to acquire public health nursing skills that enhance community strengths and a self-assessment scale for achievement. Aim This study developed a self-assessment scale for the Public Health Nursing Art to Enhance “Strength of Community” (PASC). Design This study was designed as confirmatory. Methods A draft of the scale was developed using the framework of Public Health Nursing Art to Enhance “Strength of Community,” and a self-administered questionnaire was mailed to full-time public health nurses working at 1245 sites, including the government offices of the prefectures and ordinance-designated cities/designated mid-level cities across Japan. Subsequently, item, confirmatory factor, and correlation analyses were conducted to verify the scale’s reliability and validity. Findings Content, construct, and criterion-related validities and reliability were confirmed. Conclusions This scale can measure public health nursing art to enhance public health nurses’ “strength of community.” Furthermore, reflecting on their daily activities will improve public health nurses’ skills, contributing to the community's optimal health outcomes. Clinical evidence This study developed a self-assessment scale of Public Health Nursing Art to enhance “Strength of Community.” Regarding reliability, no significant bias in the data distribution or correlations was observed and confirmed internal consistency. Regarding construct validity, the GFI, AGFI, and CFI were considered statistically acceptable.